2020
DOI: 10.1038/s41467-020-18691-3
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin del52 and ins5 knock-in mice recapitulate different myeloproliferative phenotypes observed in patients with MPN

Abstract: Somatic mutations in the calreticulin (CALR) gene are associated with approximately 30% of essential thrombocythemia (ET) and primary myelofibrosis (PMF). CALR mutations, including the two most frequent 52 bp deletion (del52) and 5 bp insertion (ins5), induce a frameshift to the same alternative reading frame generating new C-terminal tails. In patients, del52 and ins5 induce two phenotypically distinct myeloproliferative neoplasms (MPNs). They are equally found in ET, but del52 is more frequent in PMF. We gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 31 publications
8
35
0
Order By: Relevance
“…The mutCALR hom mice also developed splenomegaly and increased percentage of megakaryocytes and stem cells in the bone marrow (Figure 1). The LSK cells from mutCALR hom mice also showed proliferative advantage in a competitive bone marrow transplantation assay, as previously reported by Benlabiod et al 15 Using transgenic mice with the expression of Cre in germ line tissue, we generated mice with systemic CALR‐del52 expression ( Calr del52/+ ). The mice do not survive past embryogenesis when they are homozygous for CALR‐del52, similar to the Calr knockout mice and CRISPR/Cas9 knock‐in mice 12,16 …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The mutCALR hom mice also developed splenomegaly and increased percentage of megakaryocytes and stem cells in the bone marrow (Figure 1). The LSK cells from mutCALR hom mice also showed proliferative advantage in a competitive bone marrow transplantation assay, as previously reported by Benlabiod et al 15 Using transgenic mice with the expression of Cre in germ line tissue, we generated mice with systemic CALR‐del52 expression ( Calr del52/+ ). The mice do not survive past embryogenesis when they are homozygous for CALR‐del52, similar to the Calr knockout mice and CRISPR/Cas9 knock‐in mice 12,16 …”
Section: Discussionsupporting
confidence: 68%
“…Transgenic mice expressing human CALR‐del52 under MHC‐I promoter 13 or murine mutant CALR protein 12 have a relatively mild increase in platelets. However, transgenic mice expressing mouse‐human hybrid CALR mutant proteins generated by” knock‐in” strategy similar to ours, 14,15 developed a myeloproliferative disease which was more severe in homozygous mice. Similarly, the phenotype in the mutCALR hom mice was characterized by increased platelets and WBC and reduced RBC in the peripheral blood.…”
Section: Discussionmentioning
confidence: 74%
“…We also observed a reduction of thrombocytosis in the treated mice of the three MF models (Supplemental Figures 1G, H, I) and the number of megakaryocytes quantified after von Willebrand factor (vWF) staining was strikingly reduced in both the BM and the spleen in the JAK2 V617F model (Supplemental Figure 2A and B). We recently reported MK hyperplasia in CALRdel52 mice models (36). We confirmed here that the size of MK is particularly high in this model and we observed that pioglitazone treatment restore a normal MK size and also led to a significant reduction (2.2 fold) in the density of BM MK, suggesting an effect on MK proliferation and hyperplasia (Supplemental Figure 2C).…”
Section: Resultssupporting
confidence: 88%
“…This result is comparable to what is observed in the CALRdel52 and CALRins5 KI mouse models or in the bone marrow model after retroviral transfer, and probably explains the lower severity of the disease in the case of CALRins5 . 9 , 16 Altogether, iPSC represent a valuable tool for MPN modeling, mimicking the 2 different diseases driven either by JAK2 V617F or CALRdel52/ins5 . Indeed, iPSC showed phenotypes that correlate with clinical features in patients: a MK phenotype with heterozygous JAK2 V617F or CALR del52/ins5 and an additive erythroid phenotype with homozygous JAK2 V617F.…”
Section: Discussionmentioning
confidence: 99%